Manipulating Li2S Redox Kinetics and Lithium Dendrites by Core–Shell Catalysts under High Sulfur Loading and Lean‐Electrolyte Conditions - Mengmeng Zhen; Kaifeng Li; Mingyang Liu (Advanced Science)
Abstract For practical lithium–sulfur batteries (LSBs), the high sulfur loading and lean‐electrolyte are necessary conditions to achieve the high energy density. However, such extreme conditions will cause serious battery performance fading, due to the uncontrolled deposition of Li2S and lithium dendrite growth. Herein, the tiny Co nanoparticles embedded N‐doped carbon@Co9S8 core–shell material (CoNC@Co9S8NC) is designed to address these challenges. The Co9S8NC‐shell effectively captures lithium polysulfides (LiPSs) and electrolyte, and suppresses the lithium dendrite growth. The CoNC‐core not only improves electronic conductivity, but also promotes Li+ diffusion as well as accelerates Li2S deposition/decomposition. Consequently, the cell with CoNC@Co9S8NC modified separator delivers a high specific capacity of 700 mAh g−1 with a low‐capacity decay rate of 0.035% per cycle at 1.0 C after 750 cycles under a sulfur loading of 3.2 mg cm−2 and a E/S ratio of 12 µL mg−1, and a high initial areal capacity of 9.6 mAh cm−2 under a high sulfur loading of 8.8 mg cm−2 and a low E/S ratio of 4.5 µL mg−1. Besides, the CoNC@Co9S8NC exhibits an ultralow overpotential fluctuation of 11 mV at a current density of 0.5 mA cm–2 after 1000 h during a continuous Li plating/striping process.